Belonging on Campus: A Qualitative Inquiry of Asian International Students. (April 2016) - Slaten, Christopher D.; Elison, Zachary M.; Lee, Ji-Yeon; Yough, Mike; Scalise, Dominick
With the rise of Asian international students choosing to pursue higher education in the United States, research that identifies ways to promote Asian international students' sense of belonging on campus is needed. We used consensual qualitative research methodology to examine factors that contribute to university belonging in a sample of Asian international students ( N = 11) from a large university in the Midwestern United States. Through data analysis, we identified 14 categories across five domains (i.e., Interpersonal Interactions, Experiences of Acculturation, Campus Environment, Emphasis on Academic Achievement, and Intrapersonal Factors) that contributed to university belonging. Our findings highlight the importance of within-group social connection, acculturative stress, and academic success on Asian international students' sense of university belonging. We discuss differences between Asian international and domestic students' sense of belonging as well as implications for counseling psychologists, including interventions at the individual and institutional levels.